Analisis Hak-Hak Asn Pada Kantor Camat Hilimegai Kabupaten Nias Selatan (Berdasarkan Undang-Undang No. 20 tahun 2023) - Ndruru, Fincensius; Eliagus Telaumbanua, Heseziduhu Lase, Ayler Beniah Ndraha, (Pascasarjana STIE Amkop Makassar, 2025)
This research aims to analyze the implementation of the rights of the State Civil Apparatus (ASN) at the Hilimegai Sub-District Office, South Nias Regency, based on Law Number 20 of 2023. The research used a descriptive qualitative approach through observation, interviews, and documentation. The results showed that ASN rights, including legal protection, career development, and welfare, have been implemented in general, although there are still obstacles. The main obstacles include budget limitations, lack of socialization, and complicated bureaucracy. The provision of career development rights, such as training and promotion, still requires improvement in terms of transparency and program relevance. In addition, the delay in disbursement of performance allowances is a significant challenge in increasing ASN work motivation. This research recommends strengthening budget allocations, simplifying administrative procedures, and improving supervision of the implementation of ASN rights policies. With these measures, it is expected that the quality of public services can be improved, creating a conducive work environment for ASN in remote areas.